A Shape‐Variable, Low‐Temperature Liquid Metal–Conductive Polymer Aqueous Secondary Battery. (13th September 2021) - Fu, Hao; Liu, Guicheng; Xiong, Lingyun; Wang, Manxiang; Lee, Jeongwoo; Ren, Ren; Yang, Woochul; Lee, Joong Kee
Abstract: A shape‐variable aqueous secondary battery operating at low temperature is developed using Ga68 In22 Sn10 (wt%) as a liquid metal anode and a conductive polymer (polyaniline (PANI)) cathode. In the GaInSn alloy anode, Ga is the active component, while Sn and In increase the acid resistance and decrease the eutectic point to ‐19 °C. This enables the use of strongly acidic aqueous electrolytes (here, pH 0.9), thereby improving the activity and stability of the PANI cathode. Consequently, the battery exhibits excellent electrochemical performance and mechanical stability. The GaInSn–PANI battery operates via a hybrid mechanism of Ga 3+ stripping/plating and Cl − insertion/extraction and delivers a high reversible capacity of over 223.9 mAh g −1 and an 80.3% retention rate at 0.2 A g −1 after 500 cycles, as well as outstanding power and energy densities of 4300 mW g −1 and 98.7 mWh g −1, respectively. Because of the liquid anode, the battery without packaging can be deformed with a small force of several millinewtons without any capacity loss. Moreover, at approximately ‐5 °C, the battery delivers a capacity of 67.8 mAh g −1 at 0.2 A g −1 with 100% elasticity. Thus, the battery is promising as a deformable energy device at low temperatures and in demanding environments. Abstract : Deformable liquid metal‐conductive polymer aqueous rechargeable batteries are designed to operate at low temperature using a GaInSn alloy anode and a polyaniline cathode. The batteries exhibit excellent electrochemical, cycling, and deformation performance, thus demonstrating wide application prospects as deformable energy devices in both civilian and military fields.